Study on Stability and Elastic Properties of β-TiX (X=Nb, Ta) Alloys From First-Principles Calculations - Shuluo, Hou; Jiuxiao, Li; Yixue, Wang; Dongye, Yang; Zhaomei, Wan (Frontiers in Materials, 2022)
In this article, the phase stability, elastic properties, and electronic structure of the β-TiX (X = Nb, Ta) alloy body-centered cubic (bcc) structure were systematically studied with the aid of first-principles calculations. The results show that the phase stability and elastic properties of the β-TiX alloys are closely related to the contents of alloying element X. For β-TiX alloys, the contents of Nb and Ta that satisfy their mechanical stability are 10% and 13%, respectively; at room temperature, both β-TiNb and β-TiTa alloys can reach a thermodynamically stable state when the content of Nb or Ta is 25%. In terms of elastic properties, the content of alloying element X is positively correlated with the elastic constant, Young’s modulus, and shear modulus of the β-TiX alloys. The elastic modulus reaches its minimum when the X content is 25%, and the smallest direction of Young’s modulus appears in the <111> direction. The calculation results of the electronic structure show that the bonding strength between the Ti atom and X atom increases with the content of alloying element X, which leads to improvement of phase stability and elastic modulus.